The EFFECT OF SUPPORTIVE WORK ENVIRONMENT ON EMPLOYEE RETENTION WITH ORGANIZATIONAL COMMITMENT AS A MEDIATING VARIABLE AT BHAYANGKARA JAMBI HOSPITAL - Wiratama, Putri Amelia; Hasanah, Nur; Elliyana, Dessy (Journal of Business Studies and Management Review, 2025)
The main aim of the study was to empirically investigate organizational commitment in mediating the relationship between work environment support and employee retention. The questionnaire was distributed to 72 respondents who were honorary employees of Bhayangkara Jambi Hospital. The questionnaire consisted of several statement items received from previous studies to obtain responses using quantitative methodology. Statistical analysis and hypothesis testing used PLS-SEM with SmartPLS 4.0 software. The findings of the study explain that work environment support has a positive and significant effect on employee retention. In addition, organizational commitment is able to mediate the relationship between work environment support and employee retention. This study presents implications for human resource practices so that agencies continue to develop mechanisms by providing work environment support to increase employee organizational commitment, which in turn will increase employee retention. This study contributes to the existing literature on the relationship between work environment support and employee retention.